Board Member - Melanthiou, Yioula (My University, 2026)
As a member of the Board of Governors for The Junior and Senior School, my role is to contribute to the strategic oversight and governance of the school in alignment with its status as a not-for-profit organization owned by parents. https://www.tjss.ac.cy/page/?title=Governors%27+Profiles&pid=27